COMPARATIVE STUDY OF TWO NIGERIAN BEANS VARIETIES PRODUCTIVITY THROUGH DIFFERENT APPLICATION OF NODUMAX BIOFERTILIZATIO - Oke, Christiana O.; Akanbi-Gada, Mariam A.; Oluwatobi, Ayodele S.; Salihu, Bolaji Z.; Abdulhamid, Hikmat A.; Adio, Abdulrasheed A. (FUDMA Journal of Sciences, 2025)
This study investigated the effects of varying concentrations of Nodumax (0.5g, 1g and 5g) on the growth and reproductive performance of two cowpea (Vigna unguiculata) varieties—Ife brown and Ife omo at the Greenhouse of the Department of Plant and Environmental Biology, Kwara State University, Malete, Nigeria. A number of three seeds were planted per pot, and each treatment was replicated three times. Prior to planting, three concentrations [low (0.5g), high (5g) and IITA Standard inoculum of concentrations of Nodumax], were applied to the soil. Uninoculated pots served as controls. Growth parameters were assessed monthly from April to June, while reproductive traits were measured after three months. Results revealed that high Nodumax concentration (5g) significantly enhanced nodulation and biomass. For instance, Ife omo recorded the highest nodule count (34.77 ± 0.03), pod with seeds (10.38 ± 0.07), and wet weight (28.04 ± 0.17g) in June under high concentration. Similarly, Ife brown showed improved stem length (30.80 ± 0.06 cm) and number of leaves (19.60 ± 0.06). High Nodumax treatments outperformed both the IITA Standard and control, indicating a positive correlation between rhizobial concentration and plant performance. This study fills a critical gap in cowpea agronomy by demonstrating that optimized rhizobial inoculation enhances varietal productivity and supports sustainable legume-based farming systems.
Keywords: Nodumax; Vigna unguiculata; Agronomy; Cowpea